MEMPREDIKSI FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR TEKSTIL DAN GARMENT YANG TERDAFTAR DI BEI - Maria Hendriani; Dean Subhan Saleh; Rika Kartika (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
The prospect of the textile and garment sector in Indonesia is predicted to continue to decline since the last few years. The purpose of this study is to predict financial difficulties in textile and garment sector companies listed on the Indonesia Stock Exchange in 2016-2018. The independent variables used in this study are Current Ratio, Enterprise Risk Management, and Labor Costs. The Financial Distress model used in this study is the Altman Z score. This research data was obtained from the Indonesia Stock Exchange for the period 2016-2018. The sample used in this study were 12 textile and garment sector companies with saturated sampling method. The analysis technique used in this research is panel data regression. The results showed that the Current Ratio had a positive and significant effect on predicting Financial Distress, the proportion of Enterprise Risk Management had no significant effect on predicting Financial Distress, and Labor Costs had a significant negative effect on predicting Financial Distress.